Application of Logistic Differential Equation to Investigate The Extent of Emphasizing Stimulus Variation in Mathematics Instruction - Obasi, Chinedu (SJME (Supremum Journal of Mathematics Education), 2019)
The knowledge and skills in mathematics processes can be provided in an effective and systematic manner only by teaching mathematics in schools. Stimulus variation as a teaching skill is used to stimulate students’ interest and attract their attention to the lesson presentation.  Therefore, this study investigated the extent of emphasizing stimulus variation in mathematics instruction using logistic differential equation. The study adopted a developmental survey design where a cross-section of in-service mathematics teachers in Imo State numbering 94 were continuously observed and surveyed to decipher their extent of emphasizing stimulus variation in the classroom to promote teaching excellence. The observations were carried out for 14 days and the data were generated based on direct observational technique (using observation schedule). The result revealed inadequate and inconsistent emphasis of stimulus variation teaching skill in mathematics instruction. This implies that pre-service mathematics teachers seldom emphasize stimulus variation when teaching mathematics. It was recommended that mathematics teachers should always employ the skill of stimulus variation in class during instructional delivery so as to enhance students’ learning experience and satisfaction thereby promoting teaching excellence. DOI: https://doi.org/10.31235/osf.io/rthj2